NATO and European security in the context of the deteriorating situation in the Black Sea area - Dincă, Marian; Dincă, Alexandru-Marian (International Journal of Legal and Social Order, 2023)
Euro-Atlantic security has always been a priority for the North Atlantic Alliance, especially at the beginning of the 21st century, when mankind is facing a complex, dynamic and unpredictable security environment, one of profound economic and social imbalances. The conflict in Ukraine is and will remain a hot topic of the utmost interest, due to its political-military and economic-social implications, both regionally and internationally. For some years now, the entire Black Sea region has been boiling over from a geostrategic point of view, thus becoming Europe's new powder keg. Romania is deeply interested in a stable, democratic Black Sea region, closely linked to Euro-Atlantic structures.